Rekayasa Ekologi Sosial Dalam Mitigasi Dan Adaptasi Bencana Banjir di Sumatera: Sintesis Konseptual Berbasis Literatur - Andi Joko Prasetyo (Jurnal Ekologi, Masyarakat dan Sains, 2026)
Social ecological engineering is an integrative approach that unifies ecosystem management, local institutional strengthening, and community participation in flood disaster mitigation and adaptation. This study analyzes the concept and potential of social ecological engineering as a flood management framework in Sumatra through qualitative library research of 10 reputable sources (2015–2024). Findings indicate that flooding is a socio-ecological issue that cannot be resolved through technical-structural approaches alone. Social ecological engineering, through integration of ecosystem-based disaster risk reduction (Eco-DRR) and institutional transformation, can reduce vulnerability and enhance adaptive resilience. The novelty lies in developing a conceptual synthesis framework that explicitly connects social-ecological systems theory with community-based disaster policy in the Sumatran context.